The Role of Religiosity In Tax Compliance - Widarjo, Wahyu; Wicaksono, Galih (Islamic Accounting Journal, 2025)
Purpose & Objective: This study aimed to delve into the influence of religiosity on the rate of tax compliance of small food and beverage businesses in Banyuwangi Regency through 2025. Method: The study engaged a quantitative approach, involving 90 small food and beverage businesses selected purposively based on a set of pre-determined criteria. Data were obtained through a Likert-scale questionnaire and analysed using the SEM-PLS. Results & Conclusion: The analysis results exhibited a positive and significant relationship between religiosity and tax compliance. The higher rate of religiosity of respondents resulted in an enhanced tendency to comply with tax obligations, particularly among female business managers. Limitations: This study focused only on one small business sector in a particular region, excluding external factors, such as the intensity of tax education. Implications: These findings inform tax authorities and local governments to consider approaches that address religious values in strategies aiming at compliance improvement, such as involving religious leaders. Future research can focus on exploring additional variables such as the intensity of tax outreach and expanding the research area by, for example, focusing on the entire East Java region.